Kearifan Ekosistem Budaya pada Tata Ruang Lanskap Budaya Jawa Kuno di DAS Kali Brantas - Chairul Maulidi; Johannes Parlindungan Siregar (TATALOKA, 2021)
The protections for culture, natural environment and aesthetic are widely recognised as a part of sustainability. The cultural landscape were characterised by the traditional norms of the society and physical civilisation manifested in local wisdoms creating the traditional landscape and architecture. This study aimed to reconstruct the use of landscape as part of local culture representing the ancient Javanese civilization (9th to 15th century) in the Brantas River Basin. This study found how the Javanese cosmology was applied on a regional scale of space. According to the character of spatial use as well as its physical and social materials, the space of the ancient Javanese region consisted of three zones, namely: the Lower, Central and the Upper Zones. This findings was a model of local wisdom in the regional scale, as a counterpart of the contemporary notion of urban development that conceives the lanscape as a capital asset.